Tahapan Kepemimpinan Transformasional - Nur Arifah; Zainur Arifin (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
In a human life, of course, will not be separated from his responsibilities with fellow human beings and to God. According to the view of Islam, humans have a duty in the world to organize, manage and lead as caliph fi al-ardl. Transformational leadership is a form of leadership with the aim of changing the organization for the better, either changing oneself, others, teams or groups, in other words transformational leadership will be able to lead oneself, lead others, lead teams and lead groups/organizations. Thus, the leader is able to provide a performance boost for the organization beyond what is expected, with a form of transformational leadership that will certainly have an impact on the organization going forward, becoming a better and more advanced organization.